2022
DOI: 10.3389/fped.2022.868625
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Average Volume Assured Pressure Support

Abstract: Average volume assured pressure support (AVAPS) is a modality of non-invasive ventilation that enables the machine to deliver a pre-set tidal volume by adjusting the inspiratory pressure support within a set range. Data on its use in the pediatric population are limited to case reports and single centre case series. This article reviews paediatric data on use of AVAPS and highlights the need for validation to help develop specific guidelines on use of AVAPS in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A recent review of the current literature behind the use of AVAPS in the pediatric population described several studies that found the efficacy of AVAPS in several conditions compared with traditional bilevel PAP. These included an improved treatment of hypoventilation and improved adherence [ 26 ]. However, the authors noted that the body of evidence on the use of AVAPS in pediatric patients remains confined to a single center and case studies without control groups, and highlighted the need for prospective randomized controlled trials [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of the current literature behind the use of AVAPS in the pediatric population described several studies that found the efficacy of AVAPS in several conditions compared with traditional bilevel PAP. These included an improved treatment of hypoventilation and improved adherence [ 26 ]. However, the authors noted that the body of evidence on the use of AVAPS in pediatric patients remains confined to a single center and case studies without control groups, and highlighted the need for prospective randomized controlled trials [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54][55] Nocturnal gas exchange and adherence to NIV may be better with volume-assured BPAP modes compared with conventional BPAP modes, [54][55][56] however further studies are required in pediatrics to confirm these findings and to address the benefices and limitations of these hybrid modes. [57][58][59] Regarding autoset expiratory airway positive pressure modalities, they may be used in selected children with nocturnal hypoventilation and obstructive sleep apnea, however to our knowledge, no study has described their use in children.…”
Section: Bpap Devicesmentioning
confidence: 99%
“…8 However, data surrounding its use are limited to case reports and limited case series. 9 Furthermore, there is, to our knowledge, no literature or guidance surrounding the use of this modality in pediatric patients who require invasive ventilation via tracheostomy.…”
Section: Mirroring These Improvements New Innovations In Home Ventila...mentioning
confidence: 99%